The Concept of Child Education in the Family in the Book Sentuhan Parenting by BudiAshari - Adelia Paramita (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
The family plays a fundamental role as the primary institution in a child's education. However, in the modern era, parental involvement in children's education has declined due to various factors such as busy work schedules and technological advancements. This study aims to analyze Budi Ashari's concept of child education within the family.Parenting TouchThis study focuses on the role of parents and educational methods. This study uses a qualitative approach with library research methods. Data were obtained from Budi Ashari's work as the primary source and supported by relevant literature. Data analysis was conducted using content analysis techniques. The results of the study indicate that children are seen as a gift, a test, and a mandate from God that must be fulfilled responsibly by parents. Mothers play a crucial role from pregnancy through parenting by providing affection and emotional stability, while fathers act as leaders and moral guides. Educational methods such as advice, role models, and habituation are effective in shaping children's character and spiritual values. In conclusion, optimal and balanced parental involvement is crucial in shaping a strong, moral, and resilient generation capable of facing modern challenges.